Pengaruh Ukuran Perusahan, Leverage,Kepemilikan Asing Dan Profitabilitas Terhadap Transfer Pricing Pada Perusahaan Sektor Oil, Gas & Coal Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Nadhila Rahma Rustian; Syafri Syafri (Akuntansi, 2023)
Taxes are the most important way a country pays for government services. Multinational business organizations emerged as a result of the expansion of international economic activity. . This study aims to analyze the effect of company size, leverage, foreign ownership and profitability on transfer pricing in oil, gas & coal sector companies listed on the Indonesian stock exchange (bei). This type of research is quantitative, this research is using documentation method to collect data by recording and storing data from various existing sources. Based on the results of generalized linear model analysis, it shows that company size, leverage and profitability have a significant negative effect on transfer pricing. Based on the result of generalized linear model analysis, it shows that foreign ownership has insignificant influence on transfer pricing.